The Association Study between Tumor Necrosis Factor- Receptor 1 36 A/G (TNFR1 36 A/G) Gene Polymorphism and Azoospermic Infertile Men in Erbil City - Ashti Mohammad Amin Said (Zanco Journal of Pure and Applied Sciences, 2021)
Tumor necrosis factor-alpha (TNF-α) is a multifunctional cytokine that controls cellular activities related to spermatogenesis. (TNFR1) affects TNF- α activity and also may leads to gene dysfunction and male infertility. This retrospective study was done to assess the linkage of TNFR1 36 A/G gene polymorphism with idiopathic azoospermia in Erbil City. The present study was carried out on 98 infertile, 109 fertile males as healthy control. TNFR1 36 A/G gene polymorphisms were detected in all study subjects, and their seminal fluids were analyzed. Polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method is used for identify polymorphism in both cases and control groups. MspA1I restriction enzyme were digested PCR products. Digested and PCR products were analyzed by 3% gel electrophoresis for 45 minutes at 97 V. . The results of the present study showed that the incidence of AG genotype in azoospermia male higher than control groups (OR=2.069(1.154-3.708), P=0.014, this study found that G allele frequency in azoospermia men had a significant difference compared to the control group (OR=1.487 (0.992-2.170). Moreover, AG genotype and G allele associated with an increased risk of non-obstructive azoospermia in Erbil City.